Šiauliai Manor in the Context of Archaeological Research of North-Central Lithuanian Manors - Ostašenkovienė, Virginija (Acta humanitarica academiae Saulensis, 2025)
Lithuanian manors are an important area of historical and cultural heritage that has been studied for several decades from various perspectives – historical, architectural, economic, cultural, art-historical and heritage conservation. The perception of manor complexes as the objects of archaeological investigations has appeared in Lithuanian archaeology science only recently. Manors began to be more intensively studied in the last decade of the 20th century, and in the past two decades, archaeological research has been carried out annually at several dozen manor sites, ranging from small-scale to larger-scale investigations. According to data from 2023, more than 200 manor estates and manor sites have been archaeologically studied in Lithuania, 26 of them – in North-Central Lithuania. One of the main aspects of studying manors is their location within the landscape and the buildings they contain: the spatial arrangement of the manor’s buildings, their layout, construction techniques, materials used, and their functional purpose. The structures and functional zones of most manor complexes developed over several centuries – some buildings decayed on their own, others were demolished during the war and still others were rebuilt or newly constructed. Some of these changes are documented in preserved manor inventories, and more rarely in plans. Archaeological research data helps fill in the gaps of missing information. The aim of this article is to review the dynamics of archaeological research of manors in one region – North-Central Lithuania – focusing on the nature of these investigations and their most significant results, as well as to assess the possibilities of applying archaeological data to the study of the development of manor structures. For the case study, the Šiauliai manor estate was selected. Archaeological investigations indicate that the original manor complex was established in the north-eastern part of the estate, whereas at the turn of the 18th and 19th centuries, the manor buildings were relocated to its south-western section.